The Role of Astaxanthin as a Nutraceutical in Health and Age-Related Conditions - Bjørklund, Geir; Gasmi, Amin; Lenchyk, Larysa; Shanaida, Mariia; Mujawdiya, Pavan Kumar; Lysiuk, Roman; Antonyak, Halyna; Noor, Sadaf; Akram, Muhammad; Smetanina, Kateryna; Piscopo, Salva; Upy, Taras; et al. (My University, 2022)
The current review provides an up-to-date analysis of scientific data on astaxanthin (ASX) sources and experimental studies on its health benefits as a potent antioxidant in the aging process. ASX is a liposoluble carotenoid nutrient and reddish-orange pigment, naturally synthesized by numerous microalgae, yeasts, and bacteria as secondary metabolites. Provides a reddish hue to redfish and shellfish flesh that feed on ASX-producing microorganisms. The microalga Haematococcus pluvialis is the most important source for its industrial bioproduction. Due to its strong antioxidant properties, numerous investigations reported that natural ASX is a more significant antioxidant agent than other antioxidants, such as vitamin C, vitamin E, and β-carotene. Furthermore, several data show that ASX possesses important nutraceutical applications and health benefits, especially in healthy aging processes. However, further studies are needed for a deeper understanding of the potential mechanisms through which ASX could lead to its effective role in the healthy aging process, such as supporting brain health and skin homeostasis. This review highlights the current investigations on the effective role of ASX in oxidative stress, aging mechanisms, skin physiology, and central nervous system functioning, and shows the potential clinical implications related to its consumption.
Keywords: Natural Products; Chemistry; Pharmacy; Drug; astaxanthin; health benefit; human aging; antioxidant supplementation